2019
DOI: 10.4236/fns.2019.102012
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Influence of Dehulling on the Composition, Antioxidative and Functional Properties of Sorrel (<i>Hibiscus sabdariffa</i> L.) Seed

Abstract: Although animal proteins provide indispensable amino acids that the body requires for normal growth, maintenance and function, their expensiveness makes them unaffordable especially for most families in the developing countries. This has given impetus to extensive research into under-utilized protein-rich oilseeds such as sorrel as possible alternate sources of good quality protein for tackling the challenge of protein-energy malnutrition which is fast becoming a global challenge. Sorrel seed may hold great po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 38 publications
3
8
1
Order By: Relevance
“…This trend could be linked to their protein contents ( Table 1 ), where a higher level of protein allows greater entrapment of oil molecules. Similar trends were found in OAC of sorrel seed ( Ayo-Omogie & Osanbikan, 2019 ) and boiled Mucuna bean ( Mang et al, 2015 ) where dehulling increased the protein contents in the seed flours. The value obtained for OAC of FP-D is consistent with the value previously reported by Eckert et al (2019) , but higher than those reported by other studies ( Keivaninahr et al, 2021 , De Paiva Gouvêa et al, 2023 , Martinez et al, 2016 ).…”
Section: Resultssupporting
confidence: 72%
“…This trend could be linked to their protein contents ( Table 1 ), where a higher level of protein allows greater entrapment of oil molecules. Similar trends were found in OAC of sorrel seed ( Ayo-Omogie & Osanbikan, 2019 ) and boiled Mucuna bean ( Mang et al, 2015 ) where dehulling increased the protein contents in the seed flours. The value obtained for OAC of FP-D is consistent with the value previously reported by Eckert et al (2019) , but higher than those reported by other studies ( Keivaninahr et al, 2021 , De Paiva Gouvêa et al, 2023 , Martinez et al, 2016 ).…”
Section: Resultssupporting
confidence: 72%
“…The increase in the protein value of the processed fractions may be due to the breakdown of crude protein into amino acids during processing. It has been reported earlier that when food is subjected to roasting, the activity of proteolytic enzymes is increased, which hydrolyzes inherent proteins to their constituent amino acids and peptides, hence improving the availability of nutrients 15,31 . Similarly, a significant increase in protein content was observed after dehulling, which might be due to the removal of polysaccharides (cellulose, pectin) and leads to a reduction of tannin and phytate, which bind protein and the enzyme required for protein digestion, thus further result in higher protein digestibility 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Protein content was estimated using a CHNS analyzer (Vario EL, Elementar). Carbohydrate was calculated by difference method, 15 that is Carbohydrate%=100protein+ash+moisture+crudefat+fiber Total free amino acid was determined following Sadasivam and Manickam (1996) 16 . A total of 500 mg of the dried sample were extracted in 10 mL of 80% ethanol and centrifuged.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations